Transformational Leadership on Employee Performance: The Mediating Role of Islamic Work Ethics - Yulisharsasi; Jun Surjanti; Anang Kistyanto (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2022)
The purpose of the study was to analyze the effect of transformational leadership on employee performance through the Islamic work ethic of employees at the KUD Tani Bahagia, Gondang District, Mojokerto Regency, East Java, Indonesia. This type of research is quantitative research. The population in this study is the employees of KUD Tani Bahagia Gondang Mojokerto, totaling 75 employees. The data analysis technique used SEM-PLS with Smart-PLS 3.0 software. The results of the study found that transformational leadership has a positive effect on employee performance. Transformational leadership has a positive effect on Islamic work ethics. Islamic work ethic has a positive effect on employee performance. Islamic work ethic mediates the positive effect of transformational leadership on employee performance. The implication of this research is the importance of implementing a transformational leadership style in order to advance the quality of employee performance in the hope of increasing work activities, increasing and developing capital factors and strong business strategies, but also having to pay attention to human resources with good Islamic work ethics and have the value of good manners.